The Poetry of Anna Akhmatova - Ketchian, Sonia I. (1986)
The present study, the first of ist kind, goes beyond the investigation of separate pieces of verse to their intermeshing with one another in the creative output of Akhmatova to express the gist of her poetics, on the one hand, and with world literature and culture as important instruments, on the other. Includes texts in Russian, with translations into English.